Changes of body colour and tissue pigments in greenlip abalone (Haliotis laevigata Donovan) fed macroalgal diets at different temperatures. (15th September 2020) - Hoang, Thanh H.; Stone, David A. J.; Duong, Duong N.; Harris, James O.; Qin, Jian G.
Abstract: In Australia, commercially farmed greenlip abalone ( Haliotis laevigata Donovan), fed formulated diets display a faint lip and dark foot colour in comparison with wild abalone. This study evaluates the impact of macroalgal diets and water temperatures on the colour and tissue pigment deposition in farmed greenlip abalone. Three diets are (a) fresh Ulva sp., (b) a commercial diet and (c) a formulated diet of 30% of dried Ulva sp. meal supplement were used to feed 3‐year‐old greenlip abalone at either 22 or 26°C for 38 days. Abalone fed 30% dried Ulva sp. meal supplement had significantly higher the shell colour saturation than those fed fresh Ulva sp. The lip colour was deeper in abalone fed fresh Ulva sp. and was significantly more pronounced than those fed the diet containing 30% Ulva sp. meal. Abalone at 22°C had a significantly higher lip colour saturation value than those at 26°C. The foot of abalone fed fresh Ulva sp. was light gold, whereas abalone fed the 30% Ulva sp. meal or the commercial diet had a dark brown foot at 22°C. The foot colour was paler in abalone at 26°C than at 22°C. The content of β‐carotene was significantly higher in abalone fed fresh Ulva sp. than those fed the other diets. Abalone contained a higher amount of β‐carotene at 22°C than at 26°C. This study indicates that high water temperatures make foot colour paler and the fresh Ulva sp. diet can make the foot colour lighter at 22°C.